GOOGLE BARD PARA FOMENTAR EL APRENDIZAJE SIGNIFICATIVO EN LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGIA EN LAS CIENCIAS EXPERIMENTALES INFORMATICA DE LA UNIVERSIDAD TECNICA DE BABAHOYO, PERIODO ACADENICO 2023 MARZO 2024. - RUIZ DELGADO BRYAN EDUARDO (2024)
This study investigated the impact of the implementation of Google Bard in promoting meaningful learning of students in the career of pedagogy of experimental sciences and computer science at the technical university of Babahoyo during the period 2023-2024 through a survey applied to a significant sample of students were evaluated several variables that are related to the use of artificial intelligence chatbot based on language processing, The results show that most of the students use this type of tools frequently in their learning activities and consider this type of technology useful to improve meaningful learning. A positive trend towards the use of chatbots in education was also observed, since students perceive that this type of applications can provide them with immediate feedback, enriching the learning processes and thus providing a more personalized and flexible teaching, however, some students report experiencing occasional difficulties when using Google Bard in their studies. In summary, this research highlights the importance and impact of new technologies that can help enhance educational quality and foster meaningful learning.